2021
DOI: 10.3390/app11052040
|View full text |Cite|
|
Sign up to set email alerts
|

A Regularized Mixture of Linear Experts for Quality Prediction in Multimode and Multiphase Industrial Processes

Abstract: This paper proposes the use of a regularized mixture of linear experts (MoLE) for predictive modeling in multimode-multiphase industrial processes. For this purpose, different regularized MoLE were evaluated, namely, through the elastic net (EN), Lasso, and ridge regression (RR) penalties. Their performances were compared when trained with different numbers of samples, and in comparison to other nonlinear predictive models. The models were evaluated on real multiphase polymerization process data. The Lasso pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…multiphase processes) [5]. These modes can be represented in a multi-model (ensemble) structure [6]. This work focuses on modeling processes with multiple operating modes, and the proposed method was created with this in mind.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…multiphase processes) [5]. These modes can be represented in a multi-model (ensemble) structure [6]. This work focuses on modeling processes with multiple operating modes, and the proposed method was created with this in mind.…”
Section: Introductionmentioning
confidence: 99%
“…The modeling of multiple operating modes processes follows from rule-based expert systems [7]- [10], clustering [11], Mixture models (MM) [12]- [14], Gaussian mixture regression (GMR) [15], [16], or mixture of experts (MoE) [6], [17] strategies to identify the groups that represent each operational regime, then combine them according to the process's regime. Apart from rule-based expert models, none of the above works discuss using domain knowledge from operators.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We, the authors, wish to make the following corrections to our paper [1]. We have found that Equations ( 16), ( 21) and ( 22) were stated wrong in the manuscript.…”
mentioning
confidence: 99%